Searching for electronic journal articles to support academic tasks. A case study of the use of the Finnish National Electronic Library (FinELib) - Pertti Vakkari; Sana Talja (Information Research: An International Electronic Journal)
Introduction. We analyse how academic status and discipline influence the major search methods used by university academic staff for obtaining electronic articles for teaching, research and keeping up to date in their field. Method. The data consist of a nationwide Web-survey of the end-users of FinELib, The Finnish National Electronic Library. The number of respondents was 900. Analysis. Cross tabulations and multivariate analyses were used for answering research questions. Results. Keyword searching in journal and reference databases were clearly the most important access methods in all disciplines compared to browsing, chaining or obtaining material from colleagues. Academic status and discipline influenced the patterning of search methods used. Keyword searching in databases was more common in natural sciences, engineering and medicine than in other disciplines. Semi-directed searching comprised of browsing, chaining and colleagues as sources of access. It was significantly more common in humanities than in other disciplines. Conclusion. Patterns of searching for journal articles are changing because of the provision of digital information resources. In particular, the role of colleagues is diminishing.